(untitled) (Bangladesh Critical Care Journal, 2019)
Diabetes Mellitus is one of the leading non-communicable diseases all over the world including Bangladesh. Diabetes is characterized by chronic hyperglycemia and disturbances of carbohydrate, lipid and protein metabolism. Impaired lipid profile is commonly present in type 2 diabetes. We aimed to research serum lipid profile abnormalities hypothesizing that early detection and treatment of lipid abnormalitiescan minimize the risk for atherogenic cardiovascular disorder and cerebrovascular accident in patients with type 2 diabetes mellitus. This observational cross sectional study was carried out in the department of Biochemistry, Bangladesh Institute of Research & Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM).A total 105patients with T2DM of age within the range of 30-45 years were selected& their Fasting blood glucose (FBG), total cholesterol (TC), high density lipoprotein (HDL), low density lipoprotein (LDL), triglyceride (TG) and glycatedhaemoglobin (HbA1c) levels were evaluated. Significantly higher mean serum levels of TC, TG and LDL and significantly lower mean serum levels of HDL were noted in patients with diabetes . Significant correlations were observed between HbA1c value and serum levels of TC, TG and HDL (p<0.05) but no correlation of HbA1c value withlow density lipoprotein in diabetes patient.The study showed widespread lipid abnormalities in the course of diabetes triggered dyslipidemia as hypercholesterolemia, hypertriglyceridemia, elevated LDL and decreased HDL. Bangladesh Crit Care J March 2019; 7(1): 44-47